2018
DOI: 10.3892/ijo.2018.4295
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits superoxide dismutase-induced epithelial-to-mesenchymal transition via the PI3K/Akt/NF-κB pathway in pancreatic cancer cells

Abstract: Curcumin is a natural polyphenol compound derived from turmeric. It possesses multiple pharmacological properties, including antioxidant, anti-inflammatory and anti-tumor progression properties. Our recent study demonstrated that superoxide dismutase (SOD)-dependent production of hydrogen peroxide (H2O2) promoted the invasive and migratory activity of pancreatic cancer cells. However, whether curcumin suppresses SOD-induced cancer progression and the related mechanisms remains unclear. Since epithelial‑to-mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…In hepatoma cells, curcumin inhibits TGF-β1-induced EMT by suppressing Smad2 signaling pathway activation (31). A recent study also indicated that curcumin inhibits superoxide dismutase-induced migration, invasion and EMT-related gene expression in pancreatic cancer (32). In the present study, curcumin exerted an inhibitory effect on viability and EMT in MCF-7/TAMR cells and significantly attenuated H19-induced migration, invasion and EMT.…”
Section: Discussionsupporting
confidence: 62%
“…In hepatoma cells, curcumin inhibits TGF-β1-induced EMT by suppressing Smad2 signaling pathway activation (31). A recent study also indicated that curcumin inhibits superoxide dismutase-induced migration, invasion and EMT-related gene expression in pancreatic cancer (32). In the present study, curcumin exerted an inhibitory effect on viability and EMT in MCF-7/TAMR cells and significantly attenuated H19-induced migration, invasion and EMT.…”
Section: Discussionsupporting
confidence: 62%
“…For instance, curcumin sensitized gemcitabineresistant cancer cells by inhibiting the expression of the PRC2 subunit EZH2 and its related lncRNA PVT1 (35).We demonstrated that curcumin suppressed hydrogen peroxideinducedcell migration and invasion through the inhibition of the ROS/ERK/NF-κB signaling pathway (17). Curcumin was also found to inhibit superoxide dismutase-induced cancer EMT via the suppression of the PI3K/Akt/NF-κB signaling pathway in pancreatic cancer cells (14). In the present study, our data showed that curcumin inhibited the invasive and migratory abilities of pancreatic cancer cells under high glucose conditions, which maybe attributed to the EGF/ERK and EGF/Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 74%
“…Curcumin exhibits its antitumor effects via targeting multiple signaling pathways, including mitogen-activated protein kinase (MAPK), protein kinase B (Akt) and others (13). In a recent study, it was indicated that curcumin plays an important role in suppressing superoxide dismutase-induced EMT of pancreatic cancer by inhibiting the PI-3K/Akt/NF-κB signaling pathway (14). It was also confirmed that curcumin could restrain hypoxiainduced EMT via suppression of the hedgehog signaling pathway in pancreatic cancer cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Fe(II) either in lysosome or in labile iron pool (LIP) is known to catalyze Fenton reaction, yielding extremely reactive hydroxyl radicals [12]. As mentioned above, accumulating evidence shows that ROS are involved in EMT transition [1317]; however, the functions of ROS in the processes of EMT remain unclear.…”
Section: Introductionmentioning
confidence: 99%